Jupiter’s Interior with an Inverted Helium Gradient - N. Nettelmann; J. J. Fortney (The Planetary Science Journal)
Jupiter’s gravity field observed by NASA’s Juno spacecraft indicates that the density in the 10–100 GPa region is lower than one would expect from a H/He adiabat with 0.5–5× solar water abundance, as has been observationally inferred in Jupiter’s atmosphere, supported by the 2–4× solar enrichment in the heavy noble gases and other volatiles observed by the Galileo entry probe. Here, we assume that Jupiter’s envelope harbors a radiative window at ∼0.975–0.99 R _J . This outer stable layer (OSL) delays particle exchange and accelerates the cooling of the deep interior. Consequently, the He depletion at the Mbar level, where H/He phase separation occurs, would be stronger than seen in the atmosphere. We find that the inverted He gradient across the OSL leads to atmospheric heavy element abundances that are up to Δ Z _atm  = 0.03(+2× solar) higher than for adiabatic models. With an additional inverted Z gradient, Z _atm up to 3× solar is possible. Models with 1× solar Z _atm have a dilute core confined to the inner 0.2–0.3 M _J (0.4–0.5 R _J ), smaller than in adiabatic models. Models with 3× solar Z _atm have a largely homogeneous Z interior at 1× solar. The low observed atmospheric Ne/He ratio suggests that Ne is transported through the OSL as efficiently as He is, and at an enhanced diffusivity, as is characteristic of double-diffusive convection. Better knowledge of the H/He equation of state in the 10–100 GPa region and of the H/He phase diagram is needed to understand Jupiter’s interior structure.